1994
DOI: 10.1002/chin.199434085
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Trifluoromethylfluorocarbene Formation and Reactions under C2F5SiF3 Pulsed Adiabatic Compression Pyrolysis.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…However, others [28] have suggested that the product so labeled was really 2-C 4 F 8 ; if so, the C 4 F 8 isomer ratio was 2-> i-. Buravtsev and coworkers [5,28,30] used adiabatic compression to achieve high-temperature pulses and also observed the successive formation of c-C 4 F 8 , C 3 F 6 , and C 4 olefins over the range 700-1100 • C by GC analysis; the C 4 F 8 composition was 2-:i-:1-≈ 66:33:1. Hence we might tentatively conclude that the 2-:i-ratio is >1 in the "high-temperature regime" compared with 1 in the mediumtemperature regime.…”
Section: High-temperature Regimementioning
confidence: 97%
See 4 more Smart Citations
“…However, others [28] have suggested that the product so labeled was really 2-C 4 F 8 ; if so, the C 4 F 8 isomer ratio was 2-> i-. Buravtsev and coworkers [5,28,30] used adiabatic compression to achieve high-temperature pulses and also observed the successive formation of c-C 4 F 8 , C 3 F 6 , and C 4 olefins over the range 700-1100 • C by GC analysis; the C 4 F 8 composition was 2-:i-:1-≈ 66:33:1. Hence we might tentatively conclude that the 2-:i-ratio is >1 in the "high-temperature regime" compared with 1 in the mediumtemperature regime.…”
Section: High-temperature Regimementioning
confidence: 97%
“…These differences between perfluorocarbons and hydrocarbons can be traced largely to differences in r H, which reflect the "instability" of C 2 F 4 and the enthalpic penalty of having fluorine substituents on sp 2 -compared with sp 3 -hydridized carbons [30]. While C 2 F 4 is "unstable," the ground-state singlet carbene, 1 CF 2 :, possesses special stability [13,52,53] compared with the ground-state triplet carbene, 3 CH 2 ; the singlet-triplet splitting in CF 2 : is very large (54 kcal/mol) [75].…”
Section: Equilibrium Constraints and Contrasts With Hydrocarbon Analogsmentioning
confidence: 99%
See 3 more Smart Citations